Bioelectrical impedance analysis of body composition Applications in sports science - Marini, Elisabetta; Toselli, Stefania (UNICApress, 2021)
This book represents the result of an interdisciplinary and international effort to provide an updated overview of the theoretical and methodological principles of bioimpedance, and their applications in sports science. The structure and the writing style are intended to be useful for scholars and students in a range of academic disciplines, as well as for professionals wishing to expand and consolidate their knowledge in the field.